Alternating offer bargaining experiments with varying institutional details - Vital Anderhub; Werner Güth; Nadège Marchand (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
The game theoretic prediction for alternating offer bargaining depends crucially on how 'the pie' changes over time, and whether the proposer in a given round has ultimatum power. We study experimentally eight such bargaining games. Each game is once repeated before moving on to the next one what defines a cycle of altogether 16 successive plays. Participants play three such cycles. There are no major experience effects but strong and reliable effects of anticipated rule changes. The latter, however, are not due to strategic considerations but rather to the social norms of fairness and efficiency.
urn:nbn:de:kobv:11-10048665
Keywords: 330